Kinerja Pendidik Ditinjau Dari Dimensi Ikhlas Beramal - Herman Herman (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This study analyzes teacher[s behavior in performing duties and responsibilities at school. The result from the analysis concludes that the more sincere the teacher in performing duties and responsibilities at school, the better the work performance becomes. This conclusion was supported by the great ulama of Riyad, Saudi Arabia, Muhammad bin Ibrahim (2002:24) who contended that sincerity will be a lucky stairs, enforces gooddeeds, strenghthen the intention, and consolidates the heart to achive the desired goals. The study was conducted as a library research employing maudu'i (thematic) method, a method of tafsir studies by assembling all Qur'anic verses and hadits related to the theme studied. The goal of this study is figure out the concept of teacher's work performance in relation to sincerity for doing good deeds